Triploid Citrus Genotypes Have a Better Tolerance to Natural Chilling Conditions of Photosynthetic Capacities and Specific Leaf Volatile Organic Compounds - Lourkisti, Radia; Froelicher, Yann; Herbette, Stéphane; Morillon, Raphael; Tomi, Félix; Gibernau, Marc; Giannettini, Jean; Berti, Liliane; Santini, Jérémie (Frontiers in Plant Science, 2020)
Low temperatures during winter are one of the main constraints for citrus crop. Polyploid rootstocks can be used for improving tolerance to abiotic stresses, including cold stress. Because the produced fruit are seedless, using triploid scions is one of the most promising approaches to satisfy consumer expectations. In this study, we evaluated how the triploidy of new citrus varieties influences their sensitivity to natural chilling temperatures. We compared their behaviour to that of diploid ones, their parents (Fortune mandarin and Ellendale tangor) and one diploid clementine tree, as reference, focusing on photosynthesis parameters, oxidative metabolism and volatile organic compounds (VOC) in leaves. Triploid varieties appeared to be more tolerant than diploid ones to natural low temperatures, as evidenced by better photosynthetic properties (Pnet, gs, Fv/Fm, ETR/Pnet ratio), without relying on a better antioxidant system. The VOC levels were not influenced by chilling temperatures; however, they were affected by the ploidy level and atypical chemotypes were found in triploid varieties, with highest proportions of E-β-ocimene and linalool. Such compounds may contribute to better stress adaptation.